GAMBARAN PERILAKU KESELAMATAN PENYEBERANGAN YANG DILAKUKAN OLEH PENYEDIA JASA SPEED BOAT DI SANUR - Wirati, Ni Kadek; Antari, Gusti Ayu Ary; Rahajeng, Indah Mei (Coping: Community of Publishing in Nursing; Vol 9 No 3 (2021): Juni 2021, 2021)
The island of Nusa Penida is one of the few attractions located in the Province of Bali. Currently tourist arrivals to Nusa Penida show an increasing trend. To reach Nusa Penida, a sea transportation mode is speed boat. To Support the smooth running of tourists are needed. This study aims to determine the description of crossing safety behavior carried out by speed boat service providers in Sanur with the characteristic of age, sex, level of education,and lenght of work. The design of this study was a descriptive study using a cross-sectional method. The sample used was 43 people with consecutive sampling technique. Data collection was carried out by distributing questionnaires online to determine crossing safety behavior. The results of this study indicate that the majority of respondents have good enough behavio, as many as 24 people (55.8%). The age of respondents was dominated by the early adult age group of 18 people (41.9%). The education level of the respondents was dominated by high school gaduates as many as 24 people (55.8%). Most respondents worked more than one year, as many as 25 people (58,1%). All respondents were male. Suggestions for speed boat service providers to improve crossing safety behavior.